'He is the one who is providing you with everything so whatever he says is what you do': A Qualitative Study on Factors Affecting Secondary Schoolgirls’ Dropout in Rural Western Kenya - Oruko, Kelvin; Nyothach, Elizabeth; Zielinski-Gutierrez, Emily; Mason, Linda; Alexander, Kelly; Vulule, John; Laserson, Kayla F.; Phillips-Howard, Penelope A. (PLOS ONE, 2015)
Education is an effective way to improve girls’ self-worth, health, and productivity; however there remains a gender gap between girls’ and boys’ completion of school. The literature around factors influencing girls’ decision to stay in school is limited. Seven focus group discussions took place among 79 girls in forms 2 to 4 at secondary schools in rural western Kenya, to examine their views on why girls absent themselves or dropout from school. Data were analysed thematically. Lack of resources, sexual relationships with boyfriends, and menstrual care problems were reported to lead directly to dropout or school absence. These were tied to girls increased vulnerability to pregnancy, poor performance in school, and punishments, which further increase school absence and risk of dropout. Poverty, unmet essential needs, coercive sexual relationships, and an inequitable school environment collude to counter girls’ resolve to complete their schooling. Lack of resources drive girls to have sex with boyfriends or men who provide them with essentials their family cannot afford, such as sanitary pads and transport to school. While these improve quality of their school life, this dynamic increases their exposure to sexual risk, pregnancy, punishment, and dropout. Evaluation of interventions to ameliorate these challenges is warranted, including provision of pocket money to address their needs.